2018
DOI: 10.1111/desc.12697
|View full text |Cite
|
Sign up to set email alerts
|

Semantic detail in the developing verb lexicon: An extension of Naigles and Kako (1993)

Abstract: Verbs are often uttered before the events they describe. By 2 years of age, toddlers can learn from such an encounter. Hearing a novel verb in transitive sentences (e.g. The boy lorped the cat), even with no visual referent present, they later map it to a causative meaning (e.g. feed) (e.g. Yuan & Fisher, ). How much semantic detail does their verb representation include on this first, underinformative, encounter? Is the representation sparse, including only information for which they have evidence, or do todd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The finding that toddlers systematically extended their knowledge of transitive word order to such events suggests that children may map word order onto a broad range of asymmetries in semantic roles. This pair of studies is part of a broader effort to determine what kinds of events young children readily construe as coherent two‐participant events, and what kinds of asymmetries in those participants’ roles children readily map onto word order in transitive sentences (e.g., Arunachalam & Dennis, ; Chestnut & Markman, ; Fisher & Song, ; Gleitman, Gleitman, Miller, & Ostrin, ; Kline, Snedeker, & Schultz, ; Landau & Gleitman, ; Naigles & Kako, ).…”
Section: Testing the Predictions Of The Structure‐mapping Accountmentioning
confidence: 99%
“…The finding that toddlers systematically extended their knowledge of transitive word order to such events suggests that children may map word order onto a broad range of asymmetries in semantic roles. This pair of studies is part of a broader effort to determine what kinds of events young children readily construe as coherent two‐participant events, and what kinds of asymmetries in those participants’ roles children readily map onto word order in transitive sentences (e.g., Arunachalam & Dennis, ; Chestnut & Markman, ; Fisher & Song, ; Gleitman, Gleitman, Miller, & Ostrin, ; Kline, Snedeker, & Schultz, ; Landau & Gleitman, ; Naigles & Kako, ).…”
Section: Testing the Predictions Of The Structure‐mapping Accountmentioning
confidence: 99%
“…For example, verbs denoting a causative event (e.g., pushing) tend to take two noun arguments (a "pusher" and a "pushee"), whereas verbs that denote self-generated motion (e.g., waving) take only one noun argument (a "waver"). A large body of work has demonstrated that children are able to successfully map a predicate with two noun arguments (a transitive predicate) to a two-agent causative event, and a predicate with one noun argument (an intransitive predicate) to a one-agent noncausative event (e.g., Arunachalam & Dennis, 2019;Gertner & Fisher, 2012;Messenger et al, 2015;Naigles, 1990;Yuan & Fisher, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following similar studies (e.g., Arunachalam & Dennis, 2019; Horvath et al, 2018), we planned to analyze children's eye gaze from 1 to 2.5 s of the Response phase, which was after children had heard the test query during the Query phase, and immediately at the offset of the second prompt to find the target during the Response phase. This window is appropriate because in similar studies it takes approximately 1 s for children to settle on a scene after a central fixation, and after approximately 2.5 s, children tend to shift gaze to the scene they had not previously been fixating.…”
Section: Methodsmentioning
confidence: 99%